2018
DOI: 10.37438/jimp.v3i2.165
|View full text |Cite
|
Sign up to set email alerts
|

Membangun Aplikasi Multimedia Interaktif Dengan Model Tutorial Sebagai Sarana Pembelajaran Bahasa Kanton

Abstract: Multimedia Interaktif adalah media yang sangat kompleks dengan penggabungan dari beberapa unsur media seperti teks, grafik, gambar,foto, video, dan animasi secara berkala sehingga menjadi suatu kempulan yang menarik dan dapat mengalihkan perhatian masyarakat untuk melihatnya.Dalam laporan ini penulis akan memcoba menerapkan metode multimedia interaktif dengan model tutorial Untuk Meningkatkan Motivasi belajar Bahasa Kanton pada tenaga kerja wanita. Teknologi pembelajaran berupa multimedia ini merupakan salah s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…Thus, it can be concluded that the use of images, audio, video and animation supported the material, can provide convenience for students to understand the material and be able to attract their attention in learning, this is in line with the research conducted by [25] which explained that sound in media communication, for instance the voice of a narrator, sound effects and background sound were elements that supported the clarity of messages in the images, videos, and animations to give an impression of emphasis, happiness, sadness, and so on. [26] also revealed that the use of images, sound / audio, video and animation in learning can provide convenience for students to understand the material and was able to facilitate students who had audio, visual and kinesthetic learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be concluded that the use of images, audio, video and animation supported the material, can provide convenience for students to understand the material and be able to attract their attention in learning, this is in line with the research conducted by [25] which explained that sound in media communication, for instance the voice of a narrator, sound effects and background sound were elements that supported the clarity of messages in the images, videos, and animations to give an impression of emphasis, happiness, sadness, and so on. [26] also revealed that the use of images, sound / audio, video and animation in learning can provide convenience for students to understand the material and was able to facilitate students who had audio, visual and kinesthetic learning styles.…”
Section: Discussionmentioning
confidence: 99%
“…Pemanfaatan teknologi melalui media interaktif merupakan salah satu penyampaian informasi yang mudah menarik perhatian. Dalam penggunaannya, terdapat hubungan timpal balik antara media dan mengguna media (Kusmanagara, Marisa, & Wijaya, 2018). Media interaktif dapat disajikan dengan menggabungkan antara teks, gambar, audio dan video.…”
Section: Pendahuluanunclassified
“…Setelah melakukan semua tahapan dalam MDLC, yang terakhir adalah Pendistribusian. Tahapan yang membutuhkan pengujian untuk mendapatkan evluasi dari pengguna (user) dan sebagai pengembangan produk [15].…”
Section: ) Pendistribusian (Distribution)unclassified